THE PROBLEM OF THE HERO AND INDIVIDUAL FREEDOM IN THE ROMANTIC ERA (BASED ON SPANISH AND AZERBAIJANI LITERARY AND ARTISTIC EXAMPLES) - Gunay Bayramova (International Journal of Innovative Technologies in Social Science, 2025)
The presented article is devoted to a comparative examination of heroism and individual freedom in the Romantic period through Spanish and Azerbaijani literary examples. It is noted that Romanticism introduced a new “world‐organism” concept in opposition to the mechanistic Enlightenment worldview, foregrounding the irrational depths of the human psyche and the role of chance. From the late 18th to the mid‑19th centuries, the theme of individual freedom and the figure of the hero became a hallmark of Romantic literature.It is noted that the Napoleonic invasions, Ferdinand VII’s censorship, and the Carlist Wars (1833–1840) forced writers into exile and isolation, prompting them to place inner protest and the desire for liberty at the heart of their works. In Spanish Romantic drama, Ángel de Saavedra’s Don Álvaro o la fuerza del sino (“Don Álvaro and the Force of Fate”) is analyzed: it is noted that fatalism (“force of fate”), the conflict between love and honor, and the motif of the curse serve as the principal elements shaping the hero’s tragic destiny.Turning to Azerbaijan, it is noted that Romanticism there emerging in the late 19th and early 20th centuries was intertwined with the spirit of national liberation. Beginning with Mirza Fatali Akhundzada, individual and social freedom were brought to the forefront of literary discourse. In Hüseyn Cavid’s tragedy Səyavuş, it is noted that the hero carries not only personal idealism but also a mission to alter his people’s fate and safeguard their national and spiritual identity.The article concludes that both Spanish and Azerbaijani Romantic heroes struggle internally against constraints imposed by society, family, and inexorable fate. However, it is noted that Spanish examples tend to emphasize tragedy rooted in fatalism and curses, whereas Azerbaijani examples underscore national identity and collective freedom ideals. Thus, in the Romantic era, motifs of individual freedom and heroism are expressed in both traditions—under fatalism’s prism in Spanish theater and within the framework of national identity in Azerbaijani literature—through similarly resonant yet distinct artistic means.